A birth cohort study in the Middle East: the Qatari birth cohort study (QBiC) phase I - Eman Sadoun; Vasiliki Leventakou; Maribel Casas; Heba Fawzy Ahmed; Manolis Kogevinas; Eleni Fthenou (BMC, 2017)
Abstract Background The latest scientific reports raise concerns about the rapidly increasing burden of chronic diseases in the state of Qatar. Pregnant Qatari women often confront complications during pregnancy including gestational diabetes, hypertension, abortion and stillbirth. The investigation of early life environmental, genetic, nutritional and social factors that may affect lifelong health is of great importance. Birth cohort studies offer a great opportunity to address early life hazards and their possible long lasting effects on health. Methods/design The Qatari Birth Cohort study is the first mother-child cohort study in the Middle East Area that aims to assess the synergetic role of environmental exposure and genetic factors in the development of chronic disease and monitor woman and child health and/or obstetric characteristics with high prevalence. The present manuscript describes the recruitment phase of the study (duration: 2 years; expected number: 3000 families), where the pregnant Qatari women and their husbands are being contacted before the 15th week of gestation at the Primary Health Care Centers. The consented participants are interviewed to obtain information on several factors (sociodemographic characteristics, dietary habits, occupational/environmental exposure) and maternal characteristics are assessed based on anthropometric measurements, spirometry, and blood pressure. Pregnant women are invited to provide biological samples (blood and urine) in each trimester of their pregnancy, as well as cord blood at delivery. Fathers are also asked to provide biological samples. Discussion The present study provides invaluable insights into a wide range of early life factors affecting human health. With a geographical focus on the Middle East, it will be a resource for information to the wider scientific community and will allow the formulation of effective policies with a primary focus on public health interventions for maternal and child health.